Cervical Cancer Prevention Knowledge and Practices Among Reproductive-Age Women: A Cross-Sectional Study at a Tertiary Hospital in Dhaka - Khatun, Fatema; Hosen, Ismail; Lipi, Laila Sharmin; Hossen, Pilot; Omi, Fardina Rahman (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
While cervical cancer is both preventable and curable if detected early, knowledge and preventive practices among reproductive-age women in Bangladesh remain largely underexplored, particularly in urban settings. This study aims to address this gap through an assessment of cervical cancer prevention knowledge and practices among female patients at a tertiary hospital in Dhaka. A cross-sectional survey was conducted at Dhaka Medical College Hospital over a one-month period, with data collected from 205 women using a semi-structured questionnaire. SPSS version 23 was utilized for data analysis, including Pearson correlation, two-sample t-test, and one-way ANOVA. The results showed that 52.7 percent of participants had high knowledge of cervical cancer prevention, while 56.1 percent exhibited poor preventive practices. A significant correlation (r = 0.52, p < 0.001) was found between knowledge and practice. Additionally, factors like level of secondary education (F = 10.52, p < 0.001), employment status (F = 10.26, p < 0.001), and monthly income (r = 0.27, p < 0.001) were significantly associated with knowledge. The findings indicate that, despite high levels of knowledge, preventive practices remain poor, highlighting the need for enhanced awareness initiatives and behavior change interventions aimed at improving cervical cancer prevention. This disconnect between awareness and practice underscores the importance of designing culturally sensitive and accessible behavior change interventions, particularly targeting populations with lower educational attainment and those who are unemployed, to translate knowledge into sustained preventive practices.